The Water and Sediment Quality of Chanos chanos Monoculture and Chanos chanos - Gracilariopsis bailinae Biculture in Pond - Alcantara, Lota (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
A short-term study on the physical-chemical parameters in Chanos chanos monoculture and its biculture with Gracilariopsis bailinae indicated that the biculture might be advantageous for the growth of milkfish. Dissolved oxygen of the biculture and monoculture was not significantly different early in the morning. Oxygen produced by G. bailinae from late afternoon until evening was probably compensated by larger C. chanos that consumed more oxygen in the biculture. The afternoon DO of the biculture, however, was higher than that of the monoculture. There was no difference in pH readings between the monoculture and the biculture. Water temperature ranged from 23 - 39oC, and salinity ranged from 14 - 42% for both monoculture and biculture. The presence of G. bailinae did not affect water pH, temperature, and salinity of the biculture pond. During the culture period, phosphate in the water of the biculture decreased while it increased in the monoculture. The change in nitrate was insignificant for both monoculture and biculture. The ammonium decrease in the biculture was higher than that in the monoculture while the rise in phosphorus in the sediment was higher in the monoculture than in the biculture. The increase in nitrate and ammonia was higher in the monoculture sediments than in biculture sediments, but the difference was insignificant. Some of the phosphate and ammonium lost in the biculture pond may be attributed to the phosphorus and the nitrogen utilized by the red seaweed or stored in its tissues. Chanos chanos grew better in biculture with G. bailinae as the effect of more favorable water and sediment quality in the pond during the culture period. Furthermore, the nutrients present in the pond water and sediment were probably utilized by G. bailinae for their growth or stored in their tissues.
Keywords: Chanos chanos; Gracilariopsis bailinae; water quality; sediment quality; monoculture; biculture